Elevated serum α-synuclein autoantibodies in patients with Parkinson’s disease relative to Alzheimer’s disease and controls - Shalash, Ali; Salama, Mohamed; Makar, Marianne; Roushdy, Tamer; Elrassas, Hannan hany; Mohamed, Wael Mohamed Yousef; ElBalkimy, Mahmoud; Abu Donia, Mohamed (Frontiers Media S.A., 2017)
Early diagnosis of neurodegenerative diseases is of paramount importance for successful treatment. Lack of sensitive and early biomarkers for diagnosis of diseases like Parkinson’s disease (PD) is a handicapping problem for all movement disorders specialists. Using serum autoimmune antibodies (AIAs) against neural proteins is a new promising strategy to diagnose brain disorders through non-invasive and cost-effective method. In the present study, we measured the level of AIAs against α-synuclein (α-syn), which is an important protein involved in the pathogenesis of PD. In our study patients with PD (46 patients), Alzheimer’s disease (AD) (27 patients) and healthy controls (20 patients) were evaluated according to their sera α-syn AIAs levels. Interestingly, α-syn AIAs were significantly elevated in PD group compared to AD and healthy controls, which advocates their use for diagnosis of PD.